Persepsi Etis Mahasiswa Akuntansi Atas Perilaku Tidak Etis Akuntan - Lestari, Kadek Indah Dwi; Ramantha, I Wayan (E-Jurnal Akuntansi, 2019)
The research objective was to determine the effect of knowledge of ethics, idealism, relativism and gender on accounting students 'ethical perceptions of accountants' unethical behavior. This research was conducted at the Faculty of Economics and Business, Udayana University. The number of samples used amounted to 94 accounting students with multiple linear regression analysis techniques. Based on the results of the study it was found that knowledge of ethics and idealism negatively affected accounting students' ethical perceptions of accountant's unethical behavior. This shows that the higher the knowledge of ethics and idealism that students have, the more they disagree with the ethical behavior of accountants. Relativism has a positive effect on accounting students 'ethical perceptions of accountants' unethical behavior. This shows that the higher the relativism that students have, the more they agree with the ethical behavior of accountants. Gender has a negative but not significant effect on accounting students 'ethical perceptions of accountants' unethical behavior. This shows that men and women give an attitude of disagreement with accountants' unethical behavior. Keywords: Ethical knowledge, idealism, relativism, gender, ethical perceptions, accounting students, unethical behaviour